Peran donepezil dalam terapi penyakit alzheimer - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1999)
Neurotransmission system impairment is the prominent factor in the pathophysiology of Alzheimer's disease. Neurotransmission is the basis for information processing in the central nervous system. Communication between neurons are mediated by specific neurotransmitters. The improvement of dementia, especially dementia of the Alzheimer's type, may be achieved by increasing the ammount of cholinergic neurotransmission. The choice of treatment included administration of agonist or precursor of acetylcholine and cholinesterase inhibitors. Tacrine and donepezil are the acetylcholinesterase inhibitors approved for the treatment of Alzheimer's disease. The question is : how does donepezil influence the outcome of dementia therapy? The aim of this present study is to express the role of donepezil on the treatment of Alzheimer's disease compared with tacrine, its previous acetyicholinesterase inhibitor. In conclusion, donepezil may improve cognitive functions in Alzheimer's disease. It seems that in some aspects donepezil is superior to tacrine which has been marketed earlier.